(untitled) (International Journal of Engineering and Computer Science, 2017)
Ad hoc network is a multi-hop wireless network, which consists of number of mobile nodes. Mobile adhoc networks may be used in areas with little or no communication infrastructure This paper includes various routing protocols in MANET.our work prompted classification of varoius routing protocols in unicast and multicast routing protocols in MANET and finally our review focused on different tree based routing protocols in adhoc networks. Mobile ad hoc networks are networks which routing is based on multi-hop routing from a source to a destination node or nodes. Each of these protocols is designed to perform its task as well as it is possible according to its design criteria. This Paper deals with a classification of ad hoc routing protocols. Routing in MANET is a critical task due to highly dynamic environment. In recent, several routing protocols have been proposed for mobile ad hoc networks.A range of literature relating to the field of MANET routing was identified which highlight existing protocols as well as the current thinking within the field and the directions researchers are moving in the future.